Identidade profissional do coordenador pedagógico: mapeamento de teses e dissertações de 2009-2019 - Santos, Dulce Helena Teixeira dos (Universidade do Vale do Rio dos Sinos, 2021)
This master's thesis, entitled "PROFESSIONAL IDENTITY OF THE PEDAGOGICAL COORDINATOR: mapping of theses and dissertations 2009- 2019", presents a study on the pedagogical coordinator and the constitution of his professional identity, whose objective is to understand the ways in which professional identity of the pedagogical coordinator has been addressed in research in Education. To reach the objective, an investigative path was elaborated based on meta-research as a methodological strategy. Metaresearch in the educational field is still little explored (MAINARDES, 2018; SILVA and GAMBOA, 2014). This methodology is intended to support research on other research. Thus, the present investigation selected between 2009 and 2019 nine studies, including nine dissertations and one thesis, aimed at the study of the pedagogical coordinator. Analyzed together, the data were organized into: general and methodological aspects, involving the objectives, authors used, investigative methods and procedures; and notions about identity, seeking to understand how aspects of the coordinator's professional identity appeared in such researches. Among the theoretical references used in the study, there are: Hall (2005); Dubar (2006); Serpa (2011); D'Avila (2007); Bauman (2001); Pepper (2002); Garcia (1999); Tardif (2012); Libâneo (2006); Silva (2015); Placo, Almeida and Sousa (2011); Novoa (2009); among others and others. The main findings are: a) there was a recurrence among the authors used, as well as an emphasis on the identity of the pedagogical coordinator, with perhaps a possible theoretical expansion through the introduction of new references, concepts and epistemological perspectives ; b) most of the analyzed thesis and dissertations used the interview and questionnaire as a scientific methodology, which points to the need for studies that invest in other investigative strategies and procedures; c) studies that address power relations as one of the constituent dimensions of social and professional identities are rare.
Keywords: Coordenador pedagógico; Identidade; Identidade profissional; Metapesquisa; Pedagogical coordinator; Identity; Professional identity; Metaresearch; ACCNPQ::Ciências Humanas::Educação